Technology-Based Academic Supervision as an Innovation in Learning Monitoring in the Society 5.0 Era - Unzilah Khumairotusshiyamah; Muhammad Durrin Ni'am; Ittaqillah Haitsuma Kunta; Yusril Ihza Saputra; Robert Edy Sudarwan (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study aims to analyze the implementation of technology-based academic supervision as an innovation in learning supervision in the Society 5.0 era, and to identify its impact on lecturer professionalism and learning effectiveness. The research method used is a qualitative approach with a case study type. Data were collected through in-depth interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that technology-based academic supervision can facilitate the process of monitoring and evaluating learning in real time, increase transparency and accountability of lecturer performance, and encourage more flexible and collaborative supervisory interactions through digital media. However, there are still obstacles in the form of limited digital literacy and technological infrastructure. The implications of this study emphasize the importance of strengthening digital competencies for lecturers and supervisors and institutional policy support to optimize technology-based supervision in improving the quality of learning in the Society 5.0 era.